PENAPISAN BAKTERIOSIN DARI BAKTERI ASAM LAKTAT ASAL BEKASAM - Desniar .; Iman Rusmana; Antonius Suwanto; Nisa Rachmania Mubarik (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
Bacteriocin is proteinaceous compound that has bactericidal action against other microorganisms. Bacteriocin-producing lactic acid bacteria (LAB) is generally considered safe for human consumption and can be applied in food preservation. One source of indigenous LAB is from Indonesian fermented fish products, bekasam. This study aimed to obtain LAB isolates from bekasam that have high potential as  producer of bacteriocin. The steps were screening of bacteriocin compound and protein precipitation using ammonium sulfate with a concentration of 0-10% to 70-80%. Screening of bacteriocin compounds of 25 isolates LAB from bekasam showed that there were 11 isolates (44%) that have the potential as  producer of bacteriocin, in which the cell-free supernatant to pH 5 and or pH 6 produce inhibitory zones on the indicator bacteria Escherichia coli, Salmonella typhimurium ATCC 14028, Bacillus cereus, Staphylococcus aureus and Listeria monocytogenes. Then, the precipitation of proteins from the cell-free supernantant was done for the selected four isolates that have the potential as  producer of bacteriocin. The supernatant and  the precipitate from yield of protein precipitation in the selected four isolates showed that inhibition zone against the indicator bacteria E. coli, S. typhimurium ATCC 14 028, and L. monocytogenes with inhibition zone around 3.0 to 10.0 mm. Inhibition zones in the supernatant and the precipitate were indication that  active compound is organic acid and bacteriocin, respectively. The highest inhibition zone of the supernatant and the precipitate of the BP(3) and SK(5) isolates against L. monocytogenes and S. typhimurium, respectively.  The highest inhibition zone of the supernatant of the BP(20) and BI(3) isolates against S. typhimurium and  S. typhimurium and E. coli, respectively. While the highest inhibition zone of precipitate of the BP(20) and BI(3) isolates were same, that is against E. coli. Each with ammonium sulfate concentrations were different.Key words: Bacteriocin, lactic acid bacteria, bekasam